Moderating effect of learning management system usage on relationship between predictors and social interaction anxiety - Mazlan, Azriaty (2017)
The use of communication technology in education has been observed to positively impact to the learning process. Previous studies within the area have mostly focused on the effect of LMS. One example of communication technology on the outcome of learning process that is highly grade-based oriented rather than acquisition of soft skill such as Social Interaction Anxiety. This study specifically investigates predictors namely extensiveness of offline social interaction, perceived ease of use in the LMS, perceived usefulness in the LMS and LMS self-efficacy on the students’ and the role of LMS usage as the moderating effect on relationship between all the predictors and social interaction anxiety. Anxiety/Uncertainty Management Theory and Technology Acceptance Model provided the theoretical foundation for this study.The research was designed as quantitative study. The data was collected from 403 undergraduates’ students at UniKL campus throughout peninsular Malaysia through self-administered questionnaire over a period of 3-month. Purposive sampling technique was employed in gathering the participants. The questionnaire was adopted from Sübasi (2003), Lederer (2000), Lin (2000), Chang and Cheung (2001), Moon’s (2001), Martin, (2008) and Mattick & Clarke, (1998). Examination of the research questions and hypotheses, relevant parts of the survey for each question or hypotheses were done through statistical tests. Descriptive statistics such as frequency, means and standard deviations were used to provide a better understanding of all the variables. Data were analyzed using Structural Equation Model (SEM). Confirmatory Factor Analysis (CFA) was used to examine construct validity and reliability of the model. Findings show that students’ social interaction anxiety is significantly related to perceived usefulness in the LMS in a direct relationship. In addition, social interaction anxiety is also significantly related to extensiveness of offline social interaction and perceived ease of use in the LMS when the moderator is present. On the other hand, negative significant correlation between social interaction anxiety is noted when students involved in offline social interaction. Thus, LMS has been identified to have a role in increasing the social interaction among students. With this, it is expected that the findings can improve the learning efficiency within educational environment through the integration of LMS into education system and its effect on the learning outcomes.